Social cohesion as the missing link between natural resource management and peacebuilding: Lessons from cocoa production in Côte d'Ivoire and Colombia - Katharina Löhr; Bujar Aruqaj; Daniel Baumert; Michelle Bonatti; Michael Brüntrup; Christian Bunn; Augusto Castro-Nunez; Giovanna Chavez-Miguel; Martha Lilia Del Rio; Samyra Hachmann; Héctor Camilo Morales Mu\~noz; Franziska Ollendorf; et al. (Sustainability, 2021)
Social cohesion plays a key role in processes of peacebuilding and sustainable development. Fostering social cohesion might present a potential to enhance the connection of natural resource management and peacebuilding and better functioning of sustainable land use systems. This contribution explores the nexus between social cohesion, natural resource management, and peacebuilding. We do so by (1) reviewing literature on the three concepts and (2) studying four different key action areas in the context of sustainable cocoa production for their potential to enhance social cohesion, namely (a) agroforestry; (b) cooperatives; (c) certification schemes; and (d) trade policies. Research is based on experience from cocoa production in two post-conflict countries, Côte d'Ivoire and Colombia. Our findings show that by fostering environmentally sustainable agricultural practices, these key action areas have a clear potential to foster social cohesion among cocoa producers and thus provide a valuable contribution to post-conflict peacebuilding in both countries. However, the actual effects strongly depend on a multitude of local factors which need to be carefully taken into consideration. Further, the focus in implementation of some of these approaches tends to be on increasing agricultural productivity and not directly on fostering cocoa farmers' wellbeing and societal relations, and hence a shift toward social objectives is needed in order to strengthen these approaches as a part of overall peacebuilding strategies.
Keywords: 630; social trust; environmental peacebuilding; sustainable development; natural resource management; sustainable cocoa production